PROFIL PENYULUHAN YANG BERSIFAT EDUKATIF MENYENANGKAN DAN BERWAWASAN LUAS DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Nugraha Permana Putra; Robiatul Adawiyah (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2019)
The current phenomenon in the community is the lack of knowledge they know and the lack of education they get, so they tend to be monotonous and only do things they usually do without doing new updates. In terms of realizing community welfare, various things need to be held that can foster a great sense of curiosity. So that people can participate in counseling or have a great sense of curiosity. Therefore, in this case, the aim of this counseling is to be able to make the community aware of the importance of having education on how to achieve prosperity. When we want to do learning to the community, there are some things that we must pay attention to so that what we want to educate can be accepted and understood well so that they are able to carry it out. The first step to consider in planning, implementing, and evaluating. If this activity is successful, renewal must continue. And if this activity is unsuccessful, the improvement must be made. This counseling can make the community more knowledgeable so that it can create new things that can benefit the welfare of the community.